Maternal exposure to air pollution before and during pregnancy related to changes in newborn's cord blood lymphocyte subpopulations. The EDEN study cohort - Baïz Nour; Slama Rémy; Béné Marie-Christine; Charles Marie-Aline; Kolopp-Sarda; Magnan Antoine; Thiebaugeorges Olivier; Faure Gilbert; Annesi-Maesano Isabella (BMC, 2011)
Abstract Background Toxicants can cross the placenta and expose the developing fetus to chemical contamination leading to possible adverse health effects, by potentially inducing alterations in immune competence. Our aim was to investigate the impacts of maternal exposure to air pollution before and during pregnancy on newborn's immune system. Methods Exposure to background particulate matter less than 10 μm in diameter (PM10) and nitrogen dioxide (NO2) was assessed in 370 women three months before and during pregnancy using monitoring stations. Personal exposure to four volatile organic compounds (VOCs) was measured in a subsample of 56 non-smoking women with a diffusive air sampler during the second trimester of pregnancy. Cord blood was analyzed at birth by multi-parameter flow cytometry to determine lymphocyte subsets. Results Among other immunophenotypic changes in cord blood, decreases in the CD4+CD25+ T-cell percentage of 0.82% (p = 0.01), 0.71% (p = 0.04), 0.88% (p = 0.02), and 0.59% (p = 0.04) for a 10 μg/m3 increase in PM10 levels three months before and during the first, second and third trimester of pregnancy, respectively, were observed after adjusting for confounders. A similar decrease in CD4+CD25+ T-cell percentage was observed in association with personal exposure to benzene. A similar trend was observed between NO2 exposure and CD4+CD25+ T-cell percentage; however the association was stronger between NO2 exposure and an increased percentage of CD8+ T-cells. Conclusions These data suggest that maternal exposure to air pollution before and during pregnancy may alter the immune competence in offspring thus increasing the child's risk of developing health conditions later in life, including asthma and allergies.